Photographing children. (Virginia : Time-Life Books, 1971)
The aim of this book is to open the reader's eyes and mind anew to the whole complex and fascinating subject of photographing children.
1. The inexhaustible subject -- 2. The ideal, the real- and the surreal -- 3. Baby pictures -- 4. Kid vs. camera -- 5. Portrait of the child -- 6. A portfolio of styles.
Includes bibliographical references and index.
Keywords: PHOTOGRAPHY